When there is no justice, we need an old HERO. The trickle-down effect of psychological capital: the moderating role of organizational justice and leaders’ age - Gojny-Zbierowska, Milena (Frontiers in Psychology, 2024)
The objective of the study was to explore the impact of leaders' ages and followers' perceptions of organizational justice (POJ) on the transfer of psychological capital (PsyCap) from leaders to followers, particularly examining how employees’ resilience is influenced by leaders’ PsyCap. While some evidence exists regarding PsyCap's trickle-down effect, the specific circumstances triggering this phenomenon remain unclear. This study investigates the relationship between followers' and leaders' PsyCap, employing the Social Cognitive Theory and considering the moderating effects of leaders' age and POJ. The study focused on leader-follower dyads within a randomly selected sample of 406 businesses, encompassing 812 respondents. The survey investigation utilized the CAPI approach. The hypothesized model underwent testing through multilevel dyadic regression analysis, employing an actor-partner interdependence model. The findings support two moderators —employees' POJ and managers' age — and highlight the cross-over effect of PsyCap. Specifically, a stronger trickle-down link is observed when a leader is older and operating within a low POJ environment. Additionally, the study revealed a positive correlation between employees' PsyCap and POJ. The development of POJ enhances employees' PsyCap and resilience, while leaders' PsyCap may compensate for organizational POJ deficiencies. This study is among the first to explore PsyCap's moderators, specifically analyzing leaders' ages and POJ as factors influencing the cross-over effect of PsyCap. By identifying previously unrecognized moderators affecting the cross-over PsyCap effect, this research contributes significantly to the PsyCap literature.